Glutamate transporter 1‐expressing glia in the rat substantia nigra—Morphometric analysis and relationships to synapses. Issue 10 (14th March 2020) - Kessler, Jean‐Pierre; Salin, Pascal; Kerkerian‐Le Goff, Lydia
Abstract: Glial cells have a major role in protecting neurons against various forms of stress. Especially, astrocytes mediate the bulk of glutamate clearance in the brain via specific membrane transporters (GLAST and GLT1), thereby preventing the occurrence of excitotoxic events. Although glutamate‐mediated mechanisms are thought to contribute to nigral dopaminergic neuron degeneration in Parkinson's disease, detailed information on the organization of glia in the substantia nigra is still lacking. The present study was performed to provide quantitative information on the organization of astroglia and on the relationships between astrocytes and excitatory synapses in the rat substantia nigra. Using immunolabeling of GLT1 and confocal imaging, we found that the substantia nigra was filled with a dense meshwork of immunoreactive astrocyte processes. Stereological analysis performed on electron microscope images revealed that the density of immunoreactive astrocyte plasma membranes was substantial, close to 1 μm 2 /μm 3, in the substantia nigra neuropil, both in the pars compacta and the pars reticulata. Excitatory synapses had on average two thirds of their perimeters free from glia, a disposition that may favor transmitter spillover. The density of glutamatergic synapses, as quantified on confocal images by the simultaneous detection of bassoon and of vesicular glutamate transporter 1 or 2, was very low (0.01 and 0.025 per μm 3 in the reticulata and compacta subdivisions, respectively). Thus the ratio of GLT1‐expressing glial membrane surface to glutamatergic synapses was very high (40–100 μm 2 ), suggesting an efficient regulation of extracellular glutamate concentrations. Abstract : The rat substantia nigra contains a dense network of GLT1‐expressing glial processes. Excitatory synapses are few and have limited glial coverage. The glial membrane to excitatory synapse ratio is high, suggesting efficient regulation of extracellular glutamate.